Perfusion Index: A Noninvasive Tool for Clinical Decision in Neonates with Suspected Sepsis? - Perri, Alessandro; Barone, Giovanni; Iannotta, Rossella; Bottoni, Anthea; Tiberi, Eloisa; Zecca, Enrico (Journal of Pediatric Infectious Diseases, 2018)
Aim This article aims to assess whether perfusion index is significantly different in infants with positive C-reactive protein and/or positive cultures compared with a control group.Methods This was a prospective observational cohort study. Perfusion index was evaluated in 80 neonates at the start of antibiotic therapy for suspected sepsis. Antibiotic therapy was started based on the antenatal history or the presence of clinical signs of sepsis such as hypo/hyperthermia, feed intolerance, lethargy, hypotonia, irregular cardiac rhythms, bradycardia, cyanosis, apnea, respiratory distress, and metabolic acidosis. A case group of 23 neonates with abnormal C- reactive protein (> 10 mg/L) and/or positive cultures (blood, liquor, or bronchoalveolar lavage cultures) was compared with a control group of 23 neonates.Results Cases (mean gestational age [GA], 33 ± 5) and controls (mean GA, 33 ± 5) were matched according to the following criteria: GA (±2 weeks), postmenstrual age (±2 weeks), early (< 72 hours), or late (> 72 hours) onset of suspected infection. Mean perfusion index was 0.8 ± 0.3 in the case group and 1.2 ± 0.4 in the control group; p-value of < 0.001.Conclusions Perfusion index can be considered a noninvasive, reproducible, and easy-to-apply tool for early diagnosis of a neonatal acute inflammation in course of sepsis.
Keywords: perfusion index; neonatal sepsis; C-reactive protein; inflammation